Usefulness of ultrasonography in the diagnosis of hematoma after primary hip arthroplasty - Jerzy Białecki; Paweł Bartosz; Wojciech Marczyński; Jan Zając (Journal of Ultrasonography, 2017)
Introduction: To date, suction drainage has been routinely used after hip joint replacement. Currently, the validity of this practice is questioned in the literature. Hematoma is a risk factor of periprosthetic infection. Post-operative ultrasonography enables precise assessment of hip joint hematoma. Aim: The aim of the study was to evaluate the usefulness of hip joint ultrasonography with respect to the validity of using suction drainage after primary hip arthroplasty. Material: Inclusion criteria: coxarthrosis. Exclusion criteria: primary and secondary coagulopathy, renal or hepatic failure and history of venous or arterial thrombosis. In total, 90 patients were enrolled. Methods: The study was prospective. The patients were assigned into groups in accordance with simple randomization. On the third day postsurgery, an ultrasound examination was conducted in all patients. Results: Deep infection was found in two patients with suction drainage. Hematoma was almost twice bigger in the drainage group. There were no statistically significant differences in the Harris Hip Score between the groups. No statistically significant differences were found between the groups in: complete blood count parameters and C-reactive protein values in the first and third day after surgery, the amount of transfused packed red blood cells, duration of hospital stay, cost of hospital stay and the relationship between osteophyte removal and hematoma size. Conclusions: Ultrasonography performed after hip replacement surgeries is useful in the assessment of hematoma. The randomized study did not reveal statistically significant differences between the group with and without drainage, thus suggesting that this practice can be abandoned, except for selected cases. Due to a short hospital stay, it is recommended to conduct an ultrasound scan in addition to routine radiography and laboratory tests in order to reduce the risk of complications.